Pruning cycles and nitrogen fertilization of coffee fields conducted in the “safra zero” system - Japiassú, Leonardo Bíscaro; Garcia, André Luiz Alvarenga; Guimarães, Rubens José; Padilha, Lílian; Carvalho, Carlos Henrique Siqueira (Coffee Science - ISSN 1984-3909, 2010)
Modern, competitive and cost effective coffee production requires plants with high productivity that are more adapted to mechanical and manual harvesting. “Safra Zero” is a cultivation system designed to limit plant height and eliminate the need for expensive harvesting during years of low productivity, which usually follow years of high productivity. This system is based on pruning cycles, nitrogen fertilization and different management methods. To evaluate the “Safra Zero” system, the following experiments were conducted in coffee fields (Coffea arabica L.) at the Procafé/MAPA Experimental Station, in Varginha, Minas Gerais state: i) Evaluation of different pruning cycles in short plants; ii) Evaluation of different pruning cycles in tall plants. Rejuvenation pruning, in which all the primary branches were cut-back severely (parrot-perching), was done in alternate years, every four years, to evaluate mean productivity. iii) Evaluation of the pruning management every two years, associated with the application of different nitrogen doses (0, 200 and 400 kg.ha-1.year-1). The different pruning cycles did not result in yield gain, compared to the control plants (without pruning). The use of different nitrogen levels after pruning, in a coffee field grown on soils with high organic matter content and traditionally fertilized with 350 kg of N per hectare per year, did not improve yield, with or without pruning.